Internationalisation of European MNCs R&D: “deglobalisation” and evolution of the locational strategies - Laurens, Patricia; Le Bas, Christian; Schoen, Antoine; Larédo, Philippe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
The aim of the paper is to track the scale and the strategy of European multinational firms related to the internationalization of their R&D. We address two questions: 1. Can we confirm the general view assuming a growing trend in the internationalisation of technology? 2. Does the “home base augmenting” dominant strategy observed in the 1990s still hold? We use a patent data set for a sample of 349 firms and two time periods 1994-1996 and 2003-2005. We find out: 1) the remaining importance of the national technological bases of MNCs, 2) R&D internationalisation is not continuously growing over the period under observation, 3) an emerging trend working to the detriment of the home base augmenting strategy.